PEMBELAJARAN MATEMATIKA BERBANTUAN SOFTWARE CABRI 3D SEBAGAI UPAYA PENINGKATAN KEMAMPUAN SPASIAL SISWA - Sholihin Abdullah Ma’sum; Evan Farhan Wahyu Puadi; Ricki Yuliardi (JUMLAHKU: Jurnal Matematika Ilmiah STKIP Muhammadiyah Kuningan, 2016)
This study aims to determine: (1) whether the spatial ability of students who use mathematical learning-assisted software Cabri 3D is better than students who use conventional learning (2) How improvement of spatial ability students who study mathematics aided software Cabri 3D (3) How is the response students towards mathematics assisted Cabri 3D software. This experimental study conducted at MTs Sindangsari in the second half for the academic year 2015/2016 with the draft nonequivalent control group design. The population in this study were all students of class VIII MTs Sindangsari. Sampling was done by using sampling techniques purposipe. From the selected sample, one class into a class experiment, ie classes given mathematics learning assisted software Cabri 3D and one class as the control class, the classes given conventional learning. Measurement of spatial ability tests performed using an instrument shaped spatial abilities test description. This instrument has qualified the validity and reliability of the instrument. The results showed (1) spatial ability of students who use mathematical learning-assisted software Cabri 3D is better than students who use conventional learning, it is based on test results mean difference using the U test which showed z count > z table (2) Improved spatial ability of students to use mathematics learning aided software Cabri 3D is better than students who use conventional learning, it is based on test results mean difference score n-gain using the t’ test that show